Penguatan Karakter Masyarakat Desa Gambuhan Melalui Implementasi Nilai-Nilai Pancasila Di Era Globalisasi - Salsabillah Suci Rahmadani; Natasya Febriany; Shalsa Ayu Shabrina; Nawang Aliawati; Bayu Bagas Hapsoro; Sudrajat Sudrajat (Jurnal Bina Desa, 2026)
Globalization brings significant changes to various aspects of life, including in the order of social and cultural values of the community. Gambuhan Village, like many other communities, faces challenges in maintaining its identity and character in the midst of globalization. This article examines efforts to strengthen the character of the Gambuhan community through the implementation of Pancasila values as an ideological foundation capable of facing global challenges. This research uses a qualitative approach with a case study method involving observation, in-depth interviews, and document analysis. The results show that the implementation of Pancasila values, such as gotong royong, social justice, and unity, can strengthen the character of the people of Gambuhan Village, making them more resilient in facing the negative influence of globalization. The conclusion of this study emphasizes the importance of the active role of the village government, community leaders, and education in internalizing the values of Pancasila in order to build a strong, ethical, and competitive community character in the era of globalization.